Vitrification as an Alternative Approach for Sperm Cryopreservation in Marine Fishes. (3rd April 2017) - Cuevas-Uribe, Rafael; Hu, E.; Daniels, Harry; Gill, Adriane O.; Tiersch, Terrence R.
Abstract: The Southern Flounder Paralichthys lethostigma is a high-value species and a promising aquaculture candidate. Because sperm volume can be limited in this species (<500 µL), new sperm cryopreservation methods need to be evaluated. Vitrification is an alternative to conventional slow-rate freezing, whereby small volumes are cryopreserved at high cooling rates (>1, 000°C/min). The goal of this work was to develop a standardized approach for vitrification of Southern Flounder sperm. The specific objectives were to (1) evaluate thawing methods and vitrification solutions, (2) evaluate the postthaw membrane integrity of sperm vitrified in different cryoprotectant solutions, (3) examine the relationship between membrane integrity and motility, and (4) evaluate the ability of vitrified sperm to fertilize eggs. From the vitrification solutions tested, the highest postthaw motility (28 ± 9% [mean ± SD]) and membrane integrity (11 ± 4%) was observed for 20% ethylene glycol plus 20% glycerol. There was no significant difference in postthaw motility of sperm thawed at 21°C or at 37°C. Fertilization from vitrified sperm in one trial yielded the same fertilization rate (50 ± 20%) as the fresh sperm control, while the sperm from the other two males yielded 3%. This is the first report of fertilization by vitrified sperm in a marine fish. Vitrification can be simple, fast, inexpensive, performed in the field, and, at least for small fishes, offers an alternative to conventional cryopreservation. Because of the minute volumes needed for ultrarapid cooling, vitrification is not presently suited as a production method for large fishes. Vitrification can be used to reconstitute lines from valuable culture species and biomedical models, conserve mutants for development of novel lines for ornamental aquaculture, and transport frozen sperm from the field to the repository to expand genetic resources. Received August 23, 2016; accepted December 22, 2016 Published online March 7, 2017